Information behavior and psychological well-being: A review of the literature on social media use - Widjaya, Shafira Nanda; Komara, Diemas Arya (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2023)
Background of the study: The impact of social media on individuals' information behavior and psychological well-being is significant. Understanding how social media use influences psychological well-being is crucial in our digitally connected environment. Purpose: This study explores the relationship between information behavior on social media and psychological well-being. It investigates how individuals' information-seeking, processing, and usage on social media affect their psychological well-being. Method: A qualitative analysis of relevant literature was conducted to gain an in-depth understanding of the impact of social media on psychological well-being. Scientific journals, research articles, and textbooks in psychology and communication were reviewed. Findings: The analysis revealed a complex relationship between information behavior and psychological well-being on social media. Active social media use can enhance psychological well-being through increased social connections and support. However, negative impacts such as social media addiction, low self-esteem, and unhealthy social comparisons can also affect psychological well-being. Conclusion: Understanding the relationship between information behavior and psychological well-being on social media is crucial for promoting healthy and responsible usage. Identifying influencing factors and developing effective interventions can enhance individuals' psychological well-being. Additionally, studying information behavior and psychological well-being on social media can help identify emerging patterns in the digital era.